PENGARUH LOAN TO DEPOSIT RATIO (LDR) DAN NON PERFORMING LOAN (NPLI) TERHADAP RETURN ON ASSET (ROA) PADA BANK SWASTA YANG TERDAFTAR DI BEI - Pindonta Nalsal; Hanifah Hanifah; Pramaulida Imanniar Fatima Hendayana (Universitas La Tansa Mashiro, 2016)
This study aims to determine the effect of variable berasalah loans (NPL) and the variable size of the entire lending volume (LDR) to the profitability of private banks in proksikan Return on Assets (ROA). The sampling technique by using research methods Descriptive Quantitative criteria listed Private Bank Indonesia Stock Exchange (BEI), presenting the financial statements and ratios in full accordance with the variables to be studied. While data collection techniques using the method of documentation as well as the type of data used is the type of secondary Private Bank annual financial statements are available on the Indonesia Stock Exchange (BEI).